Pancreatogenic diabetes: what is it and what to do about it? - Hart, Phil (Henry Stewart Talks, 2023)
Pancreatogenic diabetes, Type 3c diabetes, Acute pancreatitis, Chronic pancreatitis, Pancreatic cancer, Diagnosis of pancreatogenic diabetes, Epidemiology of diabetes in pancreatitis, Pancreatitis